Biting midges of the genus Leehelea Debenham (Diptera: Ceratopogonidae) in India - Nandi, Mou; Mazumdar, Abhijit; Chaudhuri, Prasanta K. (Zootaxa, 2012)
The genus Leehelea Debenham is newly recorded in India by four new species, Leehelea brevidensis, L. fuscilateralis, L. magnidentata and L. parvicapsula. Before this investigation, only 5 species were known worldwide and with these additions, the number of world species is raised to 9. A new key to females of all the species is presented here.